1984
DOI: 10.1021/bi00304a014
|View full text |Cite
|
Sign up to set email alerts
|

Light-induced dephosphorylation of a 33K protein in rod outer segments of rat retina

Abstract: Phosphorylated proteins may play an important role in regulating the metabolism or function of rod photoreceptors. In mammalian retinas, a photoreceptor protein of 33 000 (33K) molecular weight is phosphorylated in a cyclic nucleotide dependent manner in vitro. Since light initiates the activation of a photoreceptor-specific phosphodiesterase and a rapid reduction in guanosine cyclic 3',5'-phosphate concentration, phosphorylation of the 33K protein may be modulated by light in situ. In order to test this possi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
72
1

Year Published

1988
1988
2007
2007

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 129 publications
(78 citation statements)
references
References 23 publications
5
72
1
Order By: Relevance
“…Several previous studies suggested that Ser-73 is phosphorylated in photoreceptor cells in the dark by PKA as a result of an increase in cAMP (12)(13)(14)(15). The results reported here confirm those studies and also show that the phosphorylation in the dark is quite rapid with a t1 ⁄2 of ϳ3 min, consistent with a robust PKA activity reported previously in photoreceptor cells (12)(13)(14)(15)(16).…”
Section: Light-dependent Regulation Of Ser-54 and Ser-73 Phosphorylatsupporting
confidence: 92%
See 1 more Smart Citation
“…Several previous studies suggested that Ser-73 is phosphorylated in photoreceptor cells in the dark by PKA as a result of an increase in cAMP (12)(13)(14)(15). The results reported here confirm those studies and also show that the phosphorylation in the dark is quite rapid with a t1 ⁄2 of ϳ3 min, consistent with a robust PKA activity reported previously in photoreceptor cells (12)(13)(14)(15)(16).…”
Section: Light-dependent Regulation Of Ser-54 and Ser-73 Phosphorylatsupporting
confidence: 92%
“…Besides G t ␣, the only other reported binding partner for G t ␤␥ in photoreceptor cells is phosducin (Pdc), a 28-kDa phosphoprotein expressed at high levels in both photoreceptor cells and pinealocytes (10,11). Pdc is phosphorylated in dark-adapted photoreceptors and dephosphorylated in response to light (12). Pdc harbors consensus phosphorylation sites for cAMP-dependent protein kinase (PKA) at Ser-73 and Ca 2ϩ /calmodulin-dependent protein kinase II (CaMKII) at Ser-54, and the results of several studies indicate that PKA and CaMKII are the relevant kinases for Pdc phosphorylation (13)(14)(15)(16).…”
mentioning
confidence: 99%
“…In strong light, when maximum modulation is most desirable so that the cascade is not saturated, the net dephosphorylated state of phosducin is ensured by several synergistic mechanisms. The fall in photoreceptor cGMP levels upon illumination results in decreased levels of phosphorylated phosducin, in part because the PKA enzyme that phosphorylates phosducin is also sensitive to cGMP levels (22). Cytosolic Ca 2+ levels fall upon illumination of photoreceptors.…”
Section: Discussionmentioning
confidence: 99%
“…Pdc was first discovered as a retinal phospho-protein that was phosphorylated in the dark by cAMP-dependent protein kinase (PKA) and subsequently dephosphorylated upon exposure to light [31]. Interest in Pdc increased significantly when it was shown to co-purify from retinal extracts with the βγ subunit complex of the retinal G protein, transducin (G t βγ) [11].…”
Section: Early Observations -The Gβγ Sequestration Hypothesismentioning
confidence: 99%